The Erbium laser in the debonding of ceramics: a literature review - Zanini, Nathalia Alves; Caramel-Juvino, Amanda; Ana, Patrícia Aparecida; Zezell, Denise (Brazilian Dental Science, 2022)
Background: The debonding of crowns and ceramic veneers with laser is already a reality in the clinic. It presents benefits in comparison to traditional removal with the use of a rotating instrument; however, there is still no consolidated protocol and many professionals use it without the necessary scientific basis. Objective: The aim of this work was to perform a literature review on the debonding of indirect ceramic restorations using the Er:YAG and Er,Cr:YSGG lasers to provide clinical professionals and the scientific community a careful analysis, and also to guiding the use of irradiation at laser for such procedures. Methods: Bibliographic searches were performed in the following databases: Pubmed, Web of Science and Google Scholar. According to the inclusion criteria adopted, twenty-seven clinical and in vitro studies were selected in the period from 2007 to 2021. In the present work, the composition of the crowns and facets, as well as the types of cement and the laser irradiation protocols adopted in the selected studies is detailed. Conclusions: It was concluded that the use of erbium lasers for debonding of indirect ceramic restorations proved to be more selective and conservative when compared to removal with a rotary diamond instrument. Furthermore, it was shown to be in more efficient in debonding different types of ceramics. However, there are great variations in the “debonding” protocols, which emphasizes the need for further studies that seek to standardize the irradiation protocols considering the different clinical situations. KEYWORDS Veneers debonding; Debonding; Er,Cr:YSGG laser; Er:YAG laser; Ceramics.